(untitled) (Contemporary Journal of Social Science Review, 2025)
This study analyzes the linguistic differences between male and female characters in the film My Fair Lady (1964) through a feminist linguistic lens. Drawing upon Robin Lakoff’s theory of women’s language (2004) and Dale Spender’s critique of patriarchal discourse (1998), the research examines how language functions as a marker of gender, class, and power. Focusing on the dialogues between Eliza Doolittle and Professor Henry Higgins, the study highlights how linguistic prejudice, accent modification, and social mobility intersect within a patriarchal hierarchy. Findings suggest that women’s linguistic conformity is portrayed as essential to social acceptance, revealing the ideological bias embedded in both language and culture.